Relationship between land use and coastline change in Phetchaburi and Prachuap Khiri Khan provinces as investigated by remote sensing technique - Krittika Bunyachatphisuth (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 1999